Role of transvaginal ultrasound in assessment of endometrial pathology in patients with post-menopausal bleeding - Menon, Sudha; R, Sreekumari (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Post-menopausal bleeding (PMB) is the most distressing problem in females Endometrial thickness (EMT) as assessed by transvaginal ultrasound (TVS) aids in diagnosing endometrial pathology. This study analyses usefulness of TVS as a diagnostic tool in the evaluation of PMB. Methods: A prospective study was conducted in 100 patients. Correlation of EMT by TVS was compared with gold standard of histopathological examination (HPE) of the endometrium by fractional curettage (FC). Results: Mean age was 56.9±8.03 years and mean parity status was 2.83±1.45. Mean duration after menopause to presentation of bleeding per vaginum was 5.7±3.85 years. As per the receiver operating characteristic curve (ROC) analysis, an EMT of 10.8 mm had a high negative predictive value (99.1%) for malignancy with moderate specificity (62.79%) and high sensitivity (92.3%). Conclusions: TVS can be easily performed and is less expensive and a useful diagnostic tool in the evaluation of PMB with a cut off value of 10.8 mm EMT gives a high sensitivity (92.3%) and moderate specificity (62.79%).